(untitled) (Palimpsesto, 2017)
The challenge posed by the study of literary expressions that have emerged from diasporic processes such as Nuyorican Poetry, along with its performative dimension and its development of transcultural instances as Spanglish, leads to the need of rethinking the effectiveness of methodological approaches in literary criticism to address its subject. From this problem emerge the postulation of new theoretical and analytical categories such as "body-politics" (Mignolo and Tlostanova), which reveal to be extremely useful to address the complexity of these marginal literary expressions.